Dynamics of the 1917 October Revolution Image in Russian Educational Texts: 1918-2017 - Irina Mikhailovna Brodskaya (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article considers change of 1917 October Revolution Image in educational texts for sociohistorical disciplines that were published in Russia. A necessity to investigate the source studying potential of students’ publishing and students’ magazines, published in the period between the thirties and forties of the twentieth century is emphasised. The following categories are used to find the image of the revolution: character of the revolution; issue of property, author’s attitude to violence; results of the revolution; importance of revolution. The role of the state in formation of content, language, structural, logical and physical properties of the educational text in different historical epochs is analysed. Standardization of educational texts is defined and its types are marked. Results of educational texts analysis allowed us to form out the following stages of the 1917 October Revolution Image in educational texts of 1918-2017 years: mythmaking, rationalisation, anomy, unification.